CLINICAL AND IMMUNOLOGICAL EFFICACY OF THE RECOMBINANT INTERFERON alfa-2b OF ACUTE EPSTEIN-BARR VIRAL MONONUCLEOSIS IN PRESCHOOL CHILDREN - V. N. Timchenko; S. L. Bannova; N. M. Kalinina; O. V. Bulina; E. N. Vyzhlova; A. N. Nazarova; А. V. Fedorova (Детские инфекции (Москва))
Conducted clinical and immunological examination of 51 children with acute Epstein-Barr viral mononucleosis (EBV) in age from 1 year to 7 years. All children diagnosed with a moderate degree of the disease. In the treatment of 25 people (comparison group) used the standard treatment (pathogenetic, symptomatic), treatment 26 people (main group) included the use as antiviral and immunotropic means of the preparation of human recombinant interferon Alfa-2b in the form of rectal suppositories — VIFERON®. The immunological survey was conducted in dynamics: at the height of the disease and in the convalescence period. The blood was determined indicators of cellular immunity (leukocytes, lymphocytes, CD3+, CD4+, CD8+, CD56+, HLAII+, CD95+, CD1 6+, CD25+), the concentration of IFN-a, IFN-y, IL-4 levels in spontaneous and induced production, in the serum). At milestones children of the main group noted rapid regression of clinical symptoms, normalization of body temperature, reducing intoxication, positive dynamics lymphoproliferative syndrome), a significant reduction in bed-days, no layering respiratory viral infections. Interferon had also expressed a positive impact on the changed parameters of cellular immunity and cytokine links. At the same time, 80% of patients after basic treatment is established the predominance of Th2 type immune response, indicating a high risk of developing chronic course of EBV-mononucleosis.